EDUCATION AND INOVATION AS A DRIVER FOR RURAL DESTINATION DEVELOPMENT - Ignjatović, Aleksandar; Vujko, Aleksandra; Bojović, Radmila (Economics of Agriculture, 2023)
In this paper, authors started from the hypothesis that innovations contribute to creativity and that children become more aware of in what way they can contribute to the development of rural areas. With children, play is important, and games that strengthen the imagination and encourage children to think for themselves are one of the best ways to encourage making future, strategic decisions. The challenge was to test the game “Tesla” on older school age children from 12 to 14 years old from rural areas. 138 children from five rural schools on Fruška Gora were examined. The results showed that children from rural areas, with the help of smart devices, played the game at the same level as children from any world metropolis. What’s more, through the game, the children showed awareness of the importance of the village, staying in the village and what is needed for the village to “live”.